A195 THE CANADIAN POEM EXPERIENCE. THE FIRST 50 PATIENTS. (26th February 2020) - Rai, M; Woo, M; Bechara, R
Abstract: Background: Achalasia is a disorder of esophageal motility characterized by a loss of enteric neurons resulting in impaired relaxation of the lower esophageal sphincter and absence of esophageal peristalsis. There are no current treatments that allow for regeneration of the enteric neurons. Interventions focus primarily on lowering the LES pressure to provide symptom relief and improve quality of life. Peroral endoscopic myotomy (POEM) has emerged as a less invasive technique for performing myotomy in patients with achalasia. Aims: This study aims to assess the safety and efficacy of POEM in a Canadian tertiary care center. Methods: All consecutive patients who underwent POEM between March 2016 and May 2018 at a tertiary center were included. The primary outcome of the study was clinical success rate of POEM defined as a post-POEM Eckardt score ≤ 3 at ≥ 3 months. Adverse events were recorded according to the Clavien-Dindo grading system. Results: A total of 50 consecutive patients underwent 51 POEM procedures with a mean procedure length of 85.6±29.6 minutes. Post-POEM Eckardt scores of ≤ 3 at ≥ 3 months was achieved in 98% of patients. The incidence of pathologic reflux post-poem was 23%. The median length of hospital stay was 1 day (range 1–2 days). No major adverse events occurred. Conclusions: POEM is a safe and effective procedure for the treatment of achalasia. At a median follow up of 19.5 months, 98% of patients had sustained clinical response (Eckardt score ≤ 3). Stages of POEM. a) Injection and mucosal incision, b) submucosal tunneling c) completed tunnel, view from just above the lower esophageal sphincter (main), gastric side (right upper) and esophageal side (right lower) d) myotomy e[i]) completed myotomy f) closure with hemostatic clips. Funding Agencies: None